Multi-objective optimum design for FS welded 7039 aluminium alloy considering weld quality issues - Verma S.; Garg D.; Misra J.P.; Batra U. (My University, 2025)
The optimization techniques gain immense exposure as a potential methodology for attaining the optimal process parameters for manufacturing problems. The present study deals with optimizing approaches in analyzing and predicting the tensile behavior of friction stir welded AA7039. Rotational speed, welding speed, and tilt angle are used as input variables; ultimate tensile strength (UTS) and tensile elongation (TE) is observed as a response parameter. Central composite design (CCD) of response surface methodology (RSM) is used to perform the experiment. Multi-objective genetic algorithm (MOGA) and HMOGA (Hybrid multi-objective genetic algorithm) using goal attainment method are employed to determine the optimal values of input parameters. It is observed that both techniques give better optimal process parameters for attaining maximum values of UTS and TE. Moreover, HMOGA provides better results than MOGA owing to the presence of consistency in the solution. © 2021 Elsevier Ltd